2020
DOI: 10.3390/soilsystems4030054
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Forest Soil Acidification in the Northeastern United States and Eastern Canada: Site and Soil Factors Contributing to Recovery

Abstract: As acidic deposition has decreased across Eastern North America, forest soils at some sites are beginning to show reversal of soil acidification. However, the degree of recovery appears to vary and is not fully explained by deposition declines alone. To assess if other site and soil factors can help to explain degree of recovery from acid deposition, soil resampling chemistry data (8- to 24-year time interval) from 23 sites in the United States and Canada, located across 25° longitude from Eastern Maine to Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…Since its establishment, two hallmarks of the TLW study have been the focus on long‐term research and collaboration with other research sites from across North America and the world. Numerous cross site comparison studies (e.g., Creed et al, 2008; Hazlett et al, 2020; Kerr et al, 2012; Lawrence et al, 2015; Mitchell et al, 2010; Watmough et al, 2005) have placed the results from the TLW within a broader context of other sites with differing forest and soil types, climates and disturbance conditions. These comparisons facilitate a more comprehensive understanding of forest ecosystem processes and an ability to make generalized scientific inferences and policy decisions.…”
Section: Contributions To Science and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Since its establishment, two hallmarks of the TLW study have been the focus on long‐term research and collaboration with other research sites from across North America and the world. Numerous cross site comparison studies (e.g., Creed et al, 2008; Hazlett et al, 2020; Kerr et al, 2012; Lawrence et al, 2015; Mitchell et al, 2010; Watmough et al, 2005) have placed the results from the TLW within a broader context of other sites with differing forest and soil types, climates and disturbance conditions. These comparisons facilitate a more comprehensive understanding of forest ecosystem processes and an ability to make generalized scientific inferences and policy decisions.…”
Section: Contributions To Science and Policymentioning
confidence: 99%
“…Continuous long‐term assessment of ecosystem function is necessary to track the effects of natural and anthropogenic disturbances on forests, and to assess mitigation or adaptation policies implemented by government and industry. As examples, research from the TLW has demonstrated that the re‐measurement of ecosystem parameters over long time periods is required to evaluate the efficacy of pollution control policies, and that the initial effects of forest management can be maintained for a prolonged period after harvesting (e.g., Beall et al, 2001; Buttle, Beall, et al, 2018; Buttle, Webster, et al, 2018; Hazlett et al, 2020). Only through long‐term funding commitment by governments and other partners will we achieve a comprehensive understanding of how disturbances to forested landscapes impact ecosystems services.…”
Section: Contributions To Science and Policymentioning
confidence: 99%
“…Since its establishment two hallmarks of the TLW study have been the focus on long-term research and collaboration with other research sites from across North America and the world. Numerous cross site comparison studies (e.g., Creed, Beall, Clair, Dillon & Hesslien, 2008;Hazlett et al, 2020;Kerr et al, 2012;Lawrence et al, 2015;Mitchell et al, 2010;Watmough et al, 2005) have placed the results from the TLW in context with other sites with different forest and soil types, climates and disturbance conditions. These comparisons facilitate a more comprehensive understanding of forest ecosystem processes and an ability to make broader science inferences and policy decisions from the interpretation of the research results.…”
Section: Contributions To Science and Policymentioning
confidence: 99%
“…Continuous long-term assessment of ecosystem function is necessary to track the effects of natural and anthropogenic disturbances on forests, and to assess mitigation or adaptation policies implemented by government and industry. As examples, research from the TLW has demonstrated that the re-measurement of ecosystem parameters over long time periods is required to evaluate the efficacy of pollution control policies, and that the initial effects of forest management can be maintained for a prolonged period after harvesting (e.g., Beall, Semkin & Jeffries, 2001;Hazlett et al, 2020). Only through long-term funding commitment by governments and other partners will we achieve a comprehensive understanding of how disturbances to forested landscapes impact ecosystems services; therefore, informing rigorous science-based sustainable management of these environments.…”
Section: Contributions To Science and Policymentioning
confidence: 99%
“…In Hazlett et al [12], a large data set from sites distributed throughout the northeastern USA and eastern Canada was analyzed to determine the roles of site characteristics and inherent soil properties in controlling soil recovery. Recovery responses in upper profile pH and exchangeable Al were similar to those found by Bailey et al [8].…”
mentioning
confidence: 99%